Composite infiltrated layer and preparation method and application thereof

通过对电力金具表面进行抛丸、渗锌和渗氮处理,形成复合渗层,解决了现有技术在恶劣环境下难以保护电力金具表面的问题,实现了更高的耐磨性和耐腐蚀性能,延长了使用寿命。

CN119663170APending Publication Date: 2025-03-21STEJT GRID ELEKTRIK PAUER INZHINIRING RISERCH INSTITYUT KO LTD +3
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411851650.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect the surface of the power metal in high temperature, high humidity, dry and wet alternating and low temperature environments, resulting in peeling of zinc seepage layer, intensifying corrosion, and shortening service life.

Method used

The composite seepage layer is prepared by blasting, zinc nitriding and nitriding the surface of the power metal to form a composite seepage layer. The method includes zinc permeation treatment at a temperature of 385-455°C and nitriding treatment in a vacuum ion nitriding furnace to form a high hardness nitride layer such as Fe4N and Fe2N.

Benefits of technology

It improves the wear resistance and corrosion resistance of the surface of the power metal, extends the service life, can effectively resist corrosion in high temperature, high humidity and dry and wet environments, and ensures the reliable operation of the power system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a composite infiltrated layer and a preparation method and application thereof. The preparation method comprises the following steps: performing shot blasting treatment on the surface of an electric power fitting; performing zinc impregnation treatment on the electric power fitting after shot blasting treatment; and nitriding treatment is carried out on the electric power fitting after zinc impregnation treatment, and a composite permeation layer is formed on the surface of the electric power fitting. Corrosion resistance and aging resistance of the electric power fitting can be improved, reliable operation of an electric power system is guaranteed, and the requirement for wear resistance of the electric power fitting of an overhead transmission line is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder zincizing processing of electric power hardware, and in particular to a composite zincizing layer and a preparation method and application thereof. Background Art

[0002] Power fittings include components that transfer loads and provide protection in power systems, as well as certain devices that connect and combine power systems. Power fittings are mainly made of steel, cast iron, aluminum, and aluminum alloys. In addition to conventional atmospheric environments, the use environment of power fittings also includes high temperature and humidity, alternating dry and wet environments, and low temperature environments, which places high demands on the corrosion resistance and aging resistance of power fittings. In this context, taking measures to improve the corrosion resistance and aging resistance of power fittings is crucial to ensuring the reliable operation of power systems.

[0003] Some electrical hardware, as important connecting devices in the power transmission system, plays the role of bearing mechanical loads and electrical loads in the transmission line. During their service, they are often affected by factors such as complex wind environment and combined deadweight loads, which leads to severe wear at the connections and frequent fatigue fractures, thus causing serious power transmission accidents.

[0004] At present, there are many processes for surface strengthening treatment of components. The patent application with publication number CN104498868A adopts a multi-element alloy zinc infiltration method. The prepared multi-element metallurgical diffusion layer can reach 50-90μm. The surface hardness of the metal parts produced by the patent application is higher, the wear resistance is stronger, the elongation and toughness are greatly improved, the coating has good bonding with the substrate, and it is not easy to crack and peel off. It can adapt to high acid (alkali) application environment, and solves the problem of reduced service life of the grounding grid due to cracks and peeling of the zinc layer after transportation and on-site stretching of the galvanized disc of the grounding grid. The patent application with publication number CN111705294B adds magnesium powder to the zirconizing agent, realizes the infiltration of magnesium during the zirconizing process, forms a highly corrosion-resistant zinc-magnesium alloy phase, and greatly improves the corrosion resistance of the zirconizing layer. In the powder zirconizing agent provided in the patent application, the average content of magnesium in the zirconizing layer is guaranteed to be between 0.5wt%-20wt%, so as to ensure that the corrosion resistance of the zirconizing layer can be maximized. Compared with the ordinary zirconizing layer, the neutral salt spray resistance life of the zirconizing layer containing 0.5wt%-20wt% magnesium can be increased by dozens of times, which has extremely high engineering application value and application prospects. The patent application with publication number CN103614690A performs zirconizing treatment on ductile iron castings in a slightly heated environment, and prepares a dense zirconizing layer with a thickness of 70-110μm on its surface, which effectively enhances the corrosion resistance and wear resistance of the ductile iron castings. Patent application with publication number CN107447189A proposes a method for composite zinc diffusion on the surface of metal components, post-processing the metal components after powder zinc diffusion, and conducting salt spray tests on the samples. The experimental results show that the salt spray test of the post-treated metal components can withstand corrosion for more than 500 hours.

[0005] However, in addition to the conventional atmospheric environment, the working conditions of power fittings also include harsh environments such as high temperature and high humidity, alternating dry and wet environments, and low temperature environments. If only one type of infiltration layer is prepared on the surface of the power fittings according to the above-mentioned prior art, under its harsh working conditions, the zinc infiltration layer is easy to peel off, the power fittings are easy to be corroded, and the service life is reduced. Therefore, it is necessary to further study and develop the preparation process of the composite infiltration layer on the surface of the power fittings. Compared with a single coating, a composite coating can provide better performance, such as better wear resistance and corrosion resistance, and can play a better protective role. The existing composite infiltration layer preparation process has been developed to be relatively mature. The patent application with publication number CN117821894A uses a salt bath method to prepare a composite infiltration layer of boron infiltration layer + chromium infiltration on the surface of 304 stainless steel, which effectively improves the hardness of the infiltration layer. The patent application with publication number CN117448737A uses electroplating to form a platinum-plated layer on the surface of a nickel-based high-temperature alloy, and then uses chemical vapor deposition to treat the nickel-based high-temperature alloy of the Ni-Pt interdiffusion layer with cobalt and aluminum to obtain a Co composite modified PtAl infiltration layer. And in the process of preparing the infiltration layer, by adjusting the composition of the cobalt source, the problem of low cobalt infiltration efficiency caused by excessively high aluminizing temperature is solved. However, there are certain shortcomings in the above-mentioned composite coating preparation project. During the boronizing process, a coarse FeB phase is easily formed in the boronizing layer, resulting in poor density and continuity of the infiltration layer, which increases the brittleness of the infiltration layer and makes it easy to peel off. Electroplating of platinum often consumes a lot of energy, and there are problems such as difficulty in handling the plating solution and easy pollution of the environment. In addition, the subsequent cobalt-aluminum co-infiltration needs to be produced at extremely high temperatures, which increases the production cost. Therefore, it is necessary to propose an economical, green and environmentally friendly method for preparing a composite coating that can effectively improve the density and continuity of the surface infiltration layer and improve the adhesion of the coating. Summary of the invention

[0006] The purpose of the present invention is to provide a composite diffusion layer and its preparation method and application to overcome the problems existing in the prior art. The present invention can improve the corrosion resistance and aging resistance of power fittings, ensure the reliable operation of the power system, and meet the wear resistance requirements of power fittings for overhead transmission lines.

[0007] The present invention is achieved through the following technical solutions: A method for preparing a composite infiltration layer comprises the following steps: Shot blasting treatment is performed on the surface of electrical fittings; Conduct zinc infiltration treatment on the electrical fittings after shot blasting; The electric fittings after the zincizing treatment are subjected to nitriding treatment to form a composite nitriding layer on the surface of the electric fittings.

[0008] Furthermore, the shot blasting treatment time is 5-10 minutes, and the Ra value of the electric power fittings after shot blasting treatment is 1.6 μm-3.2 μm.

[0009] Furthermore, the temperature of the sherardizing treatment is 385-455° C., and the holding time is 2-4 hours.

[0010] Furthermore, the raw materials of the sherardizing agent used in the sherardizing treatment include, by weight: 70-78 parts of Zn powder, 23-28 parts of diluent Al2O3, and 1.8-2.2 parts of activator NH4CL.

[0011] Furthermore, the material of the power fittings is 35CrMo steel, Q235 steel or Q550 steel.

[0012] Furthermore, before the surface of the electric power fitting is subjected to shot blasting, the surface of the electric power fitting is subjected to degreasing treatment, the degreasing temperature is 335° C.-365° C., and the degreasing time is 20-40 minutes.

[0013] Furthermore, the nitriding treatment is specifically as follows: The helium-filled electrical fittings are placed under a preset vacuum condition and a first preset temperature, and then ion bombarded at a preset rate for a first preset time; A mixed gas of argon and nitrogen is introduced into the electrical fittings obtained by helium ion bombardment at a first preset pressure and a second preset temperature, and the mixture is kept warm for a second preset time; A mixed gas of ammonia and hydrogen is introduced into the electrical fittings treated with the mixed gas of argon and nitrogen at a second preset pressure and a third preset temperature, and the mixture is kept warm for a third preset time, and then cooled to room temperature.

[0014] Furthermore, the vacuum degree of the preset vacuum condition is 35-55 Pa, the first preset temperature is 325-345°C, the preset rate is 500 mL / min, and the pressure of the helium gas is 1.3×10 3 Pa, the first preset time is 20-35min.

[0015] Furthermore, the first preset pressure is 135-155 MPa, the second preset temperature is 380-410° C., the second preset time is 3-5 hours, and the volume ratio of argon to nitrogen in the argon and nitrogen mixed gas is 1:5.

[0016] Furthermore, the second preset pressure is 175-195 MPa, the third preset temperature is equal to the second preset temperature, the third preset time is 3-5h, and the volume ratio of ammonia to hydrogen in the mixed gas of ammonia and hydrogen is 1:2.

[0017] A composite infiltration layer is prepared by adopting the above preparation method.

[0018] The invention discloses an application of a composite diffusion layer on electric power fittings.

[0019] A composite infiltration layer is prepared by adopting the above preparation method.

[0020] The invention discloses an application of a composite diffusion layer on electric power fittings.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention adds zinc-diffusion + nitriding coating protection on the surface of the electric hardware. Since powder zinc-diffusion has the advantages of simple equipment, less energy consumption, low cost, good coating bonding, less pollution to the environment or even no pollution, the electric hardware is first zinc-diffused by powder zinc-diffusion, and then nitrided by powder zinc-diffusion. This can improve the wear resistance of the hardware, and also has good corrosion resistance, and can effectively resist the invasion of corrosive media. The combination of powder zinc-diffusion and ion nitriding technology can give full play to the advantages of both and further improve the surface protection performance of the electric hardware. The zinc-diffusion layer can provide good corrosion resistance, while the nitriding layer can improve the surface hardness and wear resistance. The combination of the two can form a composite nitriding layer with better comprehensive performance. The composite nitriding layer can effectively change the surface state of the electric hardware, improve the subsequent nitriding layer treatment effect and the wear resistance and corrosion resistance of the surface of the electric hardware, improve the corrosion resistance and anti-aging performance of the electric hardware, and ensure the reliable operation of the power system.

[0022] Furthermore, under the action of the sherardizing temperature of the present invention, zinc atoms gradually diffuse into the iron atom lattice on the surface of the workpiece through the vacancies or gaps in the metal lattice. During the diffusion process, part of the iron atom lattice is replaced by zinc atoms to form a solid solution, which can effectively improve the bonding strength of the coating. And under the sherardizing temperature conditions of the present invention, zinc atoms react with iron atoms to form specific compounds, such as FeZn7 (Γ phase) and FeZn13 (δ phase). These compounds can effectively block the invasion of moisture and corrosive substances, thereby protecting the metal matrix from corrosion, improving the corrosion resistance of the workpiece, and extending the service life of electrical hardware. Similar to the principle of powder sherardizing, under the nitriding process flow and set process parameters of the present invention, nitrogen atoms can form Fe4N (ε phase) and Fe2N (γ' phase) with iron atoms, etc. These phases have high hardness, can improve the wear resistance of hardware, and also have good corrosion resistance, which can effectively resist the invasion of corrosive media. DETAILED DESCRIPTION

[0023] The present invention is described in detail below: The present invention provides a method for preparing a composite infiltration layer for the surface of an electric power fitting, wherein the electric power fitting is subjected to zinc infiltration and nitriding to obtain a material with a composite infiltration layer, wherein the inner layer is a zinc infiltration layer and the surface layer is a nitriding layer. The method is simple and easy to implement, has low cost, and can well improve the wear resistance and corrosion resistance of the surface of the electric power fitting.

[0024] The specific steps include: (1) Shot blasting the surface of electrical fittings; (2) Perform zinc infiltration treatment on the electrical fittings after shot blasting; (3) The electric fittings after zincizing treatment are subjected to nitriding treatment to form a composite nitriding layer on the surface of the electric fittings.

[0025] As a more preferred embodiment, before the surface of the electric power fitting is subjected to shot blasting, the surface of the electric power fitting is subjected to degreasing treatment; The prepared electrical fittings materials include 35CrMo steel, Q235 steel and Q550 steel, etc. The surface of the electrical fittings is degreased at a degreasing temperature of 335°C-365°C and a degreasing time of 20-40 minutes to ensure that the surface of the electrical fittings is clean and free of impurities.

[0026] As a more preferred embodiment, when the surface of the electric fitting is shot blasted, the shot blasting time is 5-10 minutes to ensure that the electric fitting has a certain roughness, and the Ra value is 1.6μm-3.2μm, which is easy to prepare the diffusion layer.

[0027] As a more preferred embodiment, the sherardizing agent used for sherardizing treatment is prepared from the following raw materials according to mass parts: Zn powder is 70-78 parts, diluent Al2O3 is 23-28 parts, and activator NH4CL is 1.8-2.2 parts; the temperature of the sherardizing treatment process is 385-455°C, the insulation time is 2-4h, and after the sherardizing treatment is completed, it is cooled to room temperature with the furnace.

[0028] As a more preferred embodiment, the nitriding treatment is specifically as follows: placing the electric hardware that has been subjected to the zinc-diffusion treatment into a vacuum ion nitriding furnace, adjusting the vacuum degree of the nitriding furnace to 35-55 Pa, raising the temperature to 325-345°C, introducing helium at a pressure of 1.3×103Pa at a rate of 500ml / min for ion bombardment, and the introduction time is 20-35min. The introduction of helium can effectively increase the activity of nitrogen atoms; then adjusting the pressure of the nitriding furnace to 135-155 MPa, raising the temperature to 380-410°C, introducing a mixed gas of argon and nitrogen, the mixing ratio of argon and nitrogen being 1:5, and keeping warm for 3-5h. The addition of argon can improve the overall nitriding effect of the ion nitriding of the electric hardware; then introducing a mixed gas of ammonia and hydrogen, the mixing ratio of ammonia and hydrogen being 1:2, and pressurizing to 175-195 MPa, keep warm for 3-5h, hydrogen can adjust the nitrogen potential of the nitriding atmosphere, control the structure of the nitriding layer and activate the surface, reducing the equipment's requirements for leakage rate. After the nitriding treatment is completed, cool to room temperature with the furnace.

[0029] As a more preferred embodiment, after the composite infiltration layer is formed on the surface of the electric power fitting, the performance test of the composite infiltration layer is performed, and the performance test includes the wear resistance and corrosion resistance test of the composite infiltration layer.

[0030] The present invention adds zinc-diffusion + nitriding coating protection on the surface of the electric hardware. The electric hardware is first subjected to zinc-diffusion treatment, so that zinc atoms penetrate into the surface of the electric hardware to form a zinc-iron alloy layer. The formed zinc-iron alloy layer can effectively isolate the hardware from the external environment, reduce the intrusion of corrosive media, and thus improve the corrosion resistance. Then the electric hardware is subjected to nitriding treatment, so that nitrogen atoms penetrate into the steel surface to form a nitride layer. The nitride layer has high hardness, can improve the wear resistance of the hardware, and also has good corrosion resistance, which can effectively resist the intrusion of corrosive media. The combination of powder zinc-diffusion and ion nitriding technology can give full play to the advantages of both and further improve the surface protection performance of the electric hardware. The zinc-diffusion layer can provide good corrosion resistance, while the nitriding layer can improve the surface hardness and wear resistance. The combination of the two can form a composite nitriding layer with better comprehensive performance. The composite nitriding layer can effectively change the surface state of the electric hardware, improve the subsequent nitriding layer treatment effect and the wear resistance and corrosion resistance of the surface of the electric hardware, improve the corrosion resistance and anti-aging performance of the electric hardware, and ensure the reliable operation of the power system.

[0031] The present invention also provides a composite infiltration layer, which is prepared by the above preparation method.

[0032] The present invention also provides an application of a composite infiltration layer on electric power fittings. Applying the composite infiltration layer prepared by the present invention on electric power fittings can improve the corrosion resistance and aging resistance of the electric power fittings, ensure the reliable operation of the power system, and meet the wear resistance requirements of electric power fittings for overhead transmission lines.

[0033] The embodiments of the present invention will be described in detail below in conjunction with the examples. The implementation cases are preferred embodiments of the present invention and should not be used to limit the scope of the present invention. In the following examples, the methods and experimental equipment used are all conventional methods and instruments unless otherwise specified.

[0034] Example 1 A method for preparing a composite infiltration layer for the surface of an electric power fitting comprises the following steps: (1) Prepare electrical fittings. The material of the electrical fittings is 35CrMo steel. Degrease the surface of the electrical fittings at a degreasing temperature of 335°C for 20 minutes to ensure that the surface of the electrical fittings is clean and free of impurities.

[0035] (2) The surface of the electrical fittings is shot blasted for 5 minutes to ensure that the fittings have a certain roughness. The Ra value is 1.6 μm, which is easy to prepare the diffusion layer.

[0036] (3) The electrical fittings are subjected to zincizing treatment. The zincizing agent used in the zincizing process is prepared from the following raw materials in parts by weight: 70 parts of Zn powder, 23 parts of diluent Al2O3, and 1.8 parts of activator NH4CL; the temperature used in the zincizing process is 385°C, and the holding time is 2h. After the zincizing treatment is completed, it is cooled to room temperature with the furnace.

[0037] (4) Place the zinc-plated electrical fittings into a vacuum ion nitriding furnace, adjust the vacuum degree of the nitriding furnace to 35 Pa, increase the temperature to 325 °C, and introduce a pressure of 1.3 × 10 3 Pa of helium is used for ion bombardment, and the introduction time is 20 minutes; then the pressure of the nitriding furnace is adjusted to 135MPa, the temperature is increased to 380℃, and a mixed gas of argon and nitrogen is introduced in a ratio of 1:5, and the heat is kept for 3 hours; then a mixed gas of ammonia and hydrogen is introduced in a ratio of 1:2, the pressure is increased to 175MPa, and the heat is kept for 3 hours. After the nitriding treatment is completed, it is cooled to room temperature with the furnace.

[0038] (5) Carry out the final quality inspection of the composite carburized layer, which includes the wear resistance and corrosion resistance inspection of the composite carburized layer.

[0039] Example 2 A method for preparing a composite infiltration layer for the surface of an electric power fitting comprises the following steps: (1) Prepare electrical fittings. The fittings are made of Q235 steel. Degreasing treatment is performed on the surface of the electrical fittings. The degreasing temperature is 350°C and the degreasing time is 30 minutes to ensure that the surface of the electrical fittings is clean and free of impurities.

[0040] (2) The surface of the electrical fittings is shot blasted for 8 minutes to ensure that the fittings have a certain roughness. The Ra value is 2.4 μm, which is easy to prepare the diffusion layer.

[0041] (3) The electrical fittings are subjected to zincizing treatment. The zincizing agent used in the zincizing process is prepared from the following raw materials in parts by weight: 74 parts of Zn powder, 26 parts of diluent Al2O3, and 2.0 parts of activator NH4CL; the temperature used in the zincizing process is 415°C, and the holding time is 3 hours. After the zincizing treatment is completed, it is cooled to room temperature with the furnace.

[0042] (4) Place the zinc-plated electrical fittings into a vacuum ion nitriding furnace, adjust the vacuum degree of the nitriding furnace to 45 Pa, increase the temperature to 335 ° C, and introduce a pressure of 1.3 × 10 3Pa of helium is used for ion bombardment, and the introduction time is 30 minutes; then the pressure of the nitriding furnace is adjusted to 145MPa, the temperature is increased to 395℃, and a mixed gas of argon and nitrogen is introduced in a ratio of 1:5, and the temperature is kept for 4 hours; then a mixed gas of ammonia and hydrogen is introduced in a ratio of 1:2, the pressure is increased to 185MPa, and the temperature is kept for 4 hours. After the nitriding treatment is completed, it is cooled to room temperature with the furnace.

[0043] (5) Carry out the final quality inspection of the composite carburized layer, which includes the wear resistance and corrosion resistance inspection of the composite carburized layer.

[0044] Example 3 A method for preparing a composite infiltration layer for the surface of an electric power fitting comprises the following steps: (1) Prepare electrical fittings. The material of the electrical fittings is Q550 steel. Degrease the surface of the electrical fittings at a degreasing temperature of 365°C for 40 minutes to ensure that the surface of the electrical fittings is clean and free of impurities.

[0045] (2) The surface of the electrical fittings is shot blasted for 10 minutes to ensure that the fittings have a certain roughness. The Ra value is 3.2 μm, which is easy to prepare the diffusion layer.

[0046] (3) The electrical fittings are subjected to zincizing treatment. The zincizing agent used in the zincizing process is prepared from the following raw materials in parts by weight: 78 parts of Zn powder, 28 parts of diluent Al2O3, and 2.2 parts of activator NH4CL. The temperature used in the zincizing process is 455°C, and the holding time is 4h. After the zincizing treatment is completed, it is cooled to room temperature with the furnace.

[0047] (4) Place the zinc-plated electrical fittings into a vacuum ion nitriding furnace, adjust the vacuum degree of the nitriding furnace to 55 Pa, increase the temperature to 345 °C, and introduce a pressure of 1.3 × 10 3 Pa of helium is used for ion bombardment, and the introduction time is 35 minutes; then the pressure of the nitriding furnace is adjusted to 155MPa, the temperature is increased to 410 degrees Celsius, and a mixed gas of argon and nitrogen is introduced in a ratio of 1:5, and the temperature is kept for 5 hours; then a mixed gas of ammonia and hydrogen is introduced in a ratio of 1:2, the pressure is increased to 195 MPa, and the temperature is kept for 5 hours. After the nitriding treatment is completed, it is cooled to room temperature with the furnace.

[0048] (5) Carry out the final quality inspection of the composite carburized layer, which includes the wear resistance and corrosion resistance inspection of the composite carburized layer.

[0049] In the above embodiments, the present invention adds zinc-nitriding + nitriding coating protection on the surface of the power fittings, which can effectively change the surface state of the power fittings, improve the subsequent treatment effect of the nitriding layer and the wear resistance and corrosion resistance of the surface of the power fittings.

[0050] In addition, in the above embodiment, the present invention prepares a composite diffusion layer on electric power fittings made of different materials, which can be applied to the surface strengthening of electric power fittings made of different materials.

[0051] In the above embodiments, the present invention sets a performance test for the composite infiltration layer at the end of the method. The performance test includes wear resistance and corrosion resistance test of the composite infiltration layer, which can effectively screen out composite infiltration layers of poor quality and improve the yield.

[0052] The wear resistance parameters of the products obtained in the examples are shown in Table 1.

[0053] Table 1 Comparison of wear loss of substrate, zinc-plated layer, and composite-plated layer (25N, 45 minutes)

[0054] The corrosion resistance parameters of the products obtained in each embodiment are shown in Table 2.

[0055] Table 2 Comparison of electrochemical parameters of substrate, zinc-plated layer, and composite-plated layer

[0056] The greater the amount of wear, the greater the damage to the surface of the power fittings, and the worse the wear resistance. As can be seen from Table 1, under the test conditions of a wear load of 25N and a wear time of 45 minutes, the untreated power fittings have the largest wear; the wear of the power fittings treated with zinc infiltration is reduced compared to the untreated power fittings, but the wear is also large, indicating that the protective effect of a single zinc infiltration layer on the power fittings is limited; the wear of the composite infiltration layer is the smallest, indicating that the composite infiltration layer effectively protects the power fittings and can effectively improve the surface wear resistance of the power fittings. Samples with high corrosion potential and low corrosion current density always have better corrosion resistance. As can be seen from Table 2, the corrosion current density of the power fittings that have not been treated with zinc infiltration is the largest and the corrosion potential is the smallest, indicating that the corrosion resistance is the worst; the corrosion current density of the power fittings after zinc infiltration is reduced and the corrosion potential is increased, indicating that a single zinc infiltration plays a certain protective role; the corrosion current density of the composite infiltration layer is the smallest and the corrosion potential is the largest, indicating that the composite infiltration layer effectively protects the power fittings and can effectively improve the surface corrosion resistance of the power fittings.

[0057] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a composite infiltration layer, characterized in that: The following steps are involved: Shot blasting treatment is performed on the surface of electrical fittings; Conduct zinc infiltration treatment on the electrical fittings after shot blasting; The electric fittings after the zincizing treatment are subjected to nitriding treatment to form a composite nitriding layer on the surface of the electric fittings.

2. The method for preparing a composite infiltration layer according to claim 1, characterized in that: The shot blasting treatment time is 5-10 minutes, and the Ra value of the electric power fittings after shot blasting treatment is 1.6 μm-3.2 μm.

3. The method for preparing a composite infiltration layer according to claim 1, characterized in that: The temperature of the sherardizing treatment is 385-455° C., and the holding time is 2-4 hours.

4. The method for preparing a composite infiltration layer according to claim 1, characterized in that: Calculated by weight, the raw materials of the sherardizing agent used in the sherardizing treatment include: 70-78 parts of Zn powder, 23-28 parts of diluent Al2O3, and 1.8-2.2 parts of activator NH4CL.

5. The method for preparing a composite infiltration layer according to claim 1, characterized in that: The material of the electric power fittings is 35CrMo steel, Q235 steel or Q550 steel.

6. The method for preparing a composite infiltration layer according to claim 1, characterized in that: Before shot blasting the surface of the power fittings, the surface of the power fittings is degreased at a temperature of 335°C-365°C and a degreasing time of 20-40 minutes.

7. The method for preparing a composite infiltration layer according to claim 1, characterized in that: The nitriding treatment is specifically: The helium-filled electrical fittings are placed under a preset vacuum condition and a first preset temperature, and then ion bombarded at a preset rate for a first preset time; A mixed gas of argon and nitrogen is introduced into the electrical fittings obtained by helium ion bombardment at a first preset pressure and a second preset temperature, and the mixture is kept warm for a second preset time; The electric power fittings treated with the mixed gas of argon and nitrogen are introduced with the mixed gas of ammonia and hydrogen at a second preset pressure and a third preset temperature, kept warm for a third preset time, and then cooled to room temperature.

8. The method for preparing a composite infiltration layer according to claim 7, characterized in that: The vacuum degree of the preset vacuum condition is 35-55 Pa, the first preset temperature is 325-345°C, the preset rate is 500 mL / min, and the pressure of the helium gas is 1.3×10 3 Pa, the first preset time is 20-35min.

9. The method for preparing a composite infiltration layer according to claim 7, characterized in that: The first preset pressure is 135-155 MPa, the second preset temperature is 380-410° C., the second preset time is 3-5 hours, and the volume ratio of argon to nitrogen in the argon and nitrogen mixed gas is 1:

5.

10. The method for preparing a composite infiltration layer according to claim 7, characterized in that: The second preset pressure is 175-195 MPa, the third preset temperature is equal to the second preset temperature, the third preset time is 3-5h, and the volume ratio of ammonia to hydrogen in the mixed gas of ammonia and hydrogen is 1:

2.

11. A composite infiltration layer, characterized in that: The method is prepared by any one of claims 1 to 10.

12. Use of the composite infiltration layer according to claim 11 in electric power fittings.

Citation Information

Patent Citations

  • Sherardizing method of spherical graphite casting

    CN103614690A

  • Multi-element alloy zinc-impregnation method

    CN104498868A

  • Method for composite sheradizing of surface of metal component

    CN107447189A

  • A powdered zinc diffusion agent, corrosion-resistant metal parts, and a zinc diffusion method.

    CN111705294B

  • Co composite modified PtAl infiltrated layer suitable for nickel-based superalloy and preparation method of Co composite modified PtAl infiltrated layer

    CN117448737A